Surface Stoichiometry of Galena in Aqueous Electrolytes and its Effect on Xanthate Interactions (1aa4f43d-2367-4473-a379-1721c978594a) - Paul E. Richardson; Edwin E. Maust (Society for Mining, Metallurgy & Exploration, 1976)
Cyclic voltammetry and surface potential (photovoltage) measurements have been carried out on galena electrodes in sodium tetraborate solutions with added HC1 and NaOH to adjust the pH over the range 2 to 13. The first technique shows that the surface species formed on moderate anodic polarization and reduced on subsequent cathodic polarization are the same over the entire pH range. At anodic potentials, a soluble metal species and excess sulfur are formed; at cathodic potentials, sulfur is reduced to a soluble species. More importantly, excess surface sulfur is formed spontaneously under zero current conditions in alkaline solutions. This has been shown to occur on both polished surfaces and on virgin surfaces produced by in situ cleavage under the electrolyte. The photovoltage gives some insight into the charge and potential distribution at the galena surface. This is found to depend on past electrochemical history and the n- or p-type semiconducting character of the electrode and is interpreted in terms of changes in the surface stoichiometry that occur during reduction or oxidation. The effect of surface stoichiometry on subsequent xanthate interactions is discussed.